2013
DOI: 10.1021/jp400696f
|View full text |Cite
|
Sign up to set email alerts
|

Direct Test of the Equivalency of Dynamic IR and Dynamic Raman Spectroscopies As Techniques for Observing Ultrafast Molecular Dynamics

Abstract: We report the temperature-dependent infrared (IR) and Raman spectra of Fe(CO)3(η(4)-norbornadiene). This molecule undergoes carbonyl ligand site exchange on the vibrational time scale, and the effect of this exchange is observable as coalescence of the carbonyl bands in both the IR and Raman spectra. We outline a theory that we used to account for these effects and report simulations of the experimental spectra. We used these simulations to extract the carbonyl ligand exchange rates at various temperatures fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Most notably, in a series of impressive papers, Lear and colleagues have examined some subtle effects on the chemical exchange in the diene complexes. They have shown that Raman spectroscopy mimics the IR data, giving activation energies for NBD in 2-methylpentane of 1.2 ± 0.2 and 1.4 ± 0.1 kcal/mol from IR and Raman data, respectively. The rate constants varied from 1.15 × 10 12 s –1 at 293 K to 0.48 × 10 12 s –1 at 213 K. In other words they get essentially identical results to Grevels 1 .…”
Section: Introductionmentioning
confidence: 90%
“…Most notably, in a series of impressive papers, Lear and colleagues have examined some subtle effects on the chemical exchange in the diene complexes. They have shown that Raman spectroscopy mimics the IR data, giving activation energies for NBD in 2-methylpentane of 1.2 ± 0.2 and 1.4 ± 0.1 kcal/mol from IR and Raman data, respectively. The rate constants varied from 1.15 × 10 12 s –1 at 293 K to 0.48 × 10 12 s –1 at 213 K. In other words they get essentially identical results to Grevels 1 .…”
Section: Introductionmentioning
confidence: 90%
“…Compared with NMR, the IR spectrum has a much shorter time scale of 10 −13 s, enough to reflect information on different functional groups by presenting peaks of different shift areas on the spectrum. 18 Areas of characteristic peaks on the IR spectrogram can reflect the relative amount of corresponding substances. However, the ionicity could be determined accurately in case the standard curve was established between the peak area and quantity of substances.…”
Section: Ah(bronsted Acid) B(bronsted Base) [Bh] Amentioning
confidence: 99%
“…In several elegant experiments, Lear and co-workers 32−34 extended these experiments and essentially confirmed Grevels's conclusions. It is worth mentioning that two authors 30,32 have suggested a mistake in McClung's method, but a careful analysis of the mathematics shows that the supposed error is due only to an unconventional definition and that in fact McClung's method is essentially the same as theirs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%